KINERJA DINAS BINA MARGA DAN PENGAIRAN KABUPATEN ROKAN HULU TAHUN 2015 - Mela Rizkiana; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aim is to identify and analyze the performance of Dinas Bina Marga dan Pengairan Rokan Hulu Year 2015. The location of this research is at the Dinas Bina Marga dan Pengairan Rokan Hulu. Informants are formal leaders and informal leaders. Formal character is the head of the Dinas Bina Marga dan Pengairan Rokan Hulu, while the informal leaders that employees who are knowledgeable about research problems. In analyzing the data used descriptive method that analyzes the data by formulating and decipher and interpret based on the basic theories are closely related to the existing problems. The study states the performance of employees at the Dinas Bina Marga dan Pengairan Rokan Hulu in general can be said is good, based on the final value of the performance of each employee with the accumulated value of Target Employee Work and conduct overall job so that it can be concluded at the level " good". However, there are some shortcomings in some aspects that need to be addressed. There are also some shortcomings in the system of assessment under Regulation No. 46 of 2011 as in some aspects Appraisal that do not have clear criteria for measuring in the aspect causing a less accurate ratings, and the ratings are very subjective because it is only rated by the supervisor alone and does not involve other elements related. These ratings only measure individual performance rather than team performance, while at present more work is charged on teamwork, not on indvidu alone.Keywords: Performance, Employee, Rokan Hulu